ANALISIS DAMPAK KONSUMSI JAJANAN, AKTIFITAS FISIK, DAN STATUS GIZI TERHADAP PRESTASI BELAJAR SISWA DI SMK SWASTA PHARMACA MEDAN - Syafleni Alif (Jurnal Komunitas Kesehatan Masyarakat, 2020)
Overweight and obesity are health problems that need serious attention, because they are the fifth largest cause of death in the world. The purpose of this study is to analyze the Impact Analysis of Street Food Consumption, Physical Activity, and Nutritional Status on SMK Pharmacy in Medan. This research uses quantitative research with cross sectional study design. The location of this research was conducted at the Medan Private Vocational School. When the research took place from Juli to Oktober 2019. The population in this study were all students of class XI and class XII in the Medan SMK Pharmacy with a total of 179 students. The technique used is proportional random sampling. Survey data were analyzed using the Chi Square test and logistic regression. Based on the results of the study note that, consumption of snacks (p = 0.004), physical activity (p = 0.048), nutritional status (p = 0.001), affect the learning achievement of students at the Medan SMK Pharmy. Based on the results of the study, it can be concluded that the consumption of snacks, physical activity, nutritional status influences the learning achievement of students at the SMK Pharmacy, so that the advice in this study is expected to be used as a material consideration in making policies in conducting counseling about consumption eat snacks.